ANITA’s Text Analysis Services for Fighting Online Illegal Trafficking of Drugs, Weapons and False Charity Claims: A Lateral Thinking Approach - Masucci, Vincenzo; Colombo, Jacopo; Caterino, Ciro; Nardeli, Filippo (NBP. Nauka, bezbednosti, policija, 2022)
ANITA platform aims at improving investigation capabilities of law enforcement agencies (LEAs) by delivering a set of tools and techniques to efficiently address online illegal trafficking of counterfeit/falsified medicines, NPS, drugs, and weapons with Artificial Intelligence (AI). Expert.ai has developed a dedicated written content analysis engine to support investigative activity. Already the market offers several solutions adopting AI to detect and trace illicit markets analysing web content with NLP that automatically discover hidden substances and weapons in the text analysed. In addition to the capability of deep understanding the contents, ANITA’s approach has adopted a lateral thinking approach and the supervised generation of knowledge from the analysed contents. Rather than focusing on searching for specific proper names of substances, weapons, NPS, etc. that are constantly evolving in considerable speed, we propose to concentrate on searching for precursors, namely collateral concepts related with the target of the investigation. Is the case of accessories for weapons such as sights for rifles or glass vessels used to produce the drugs themselves. This article reports the system’s ability to automatically identify precursors and generate stimuli and knowledge, which the investigator must validate, that enhances the creative and intuitive approach (serendipity) to investigation combining the best of the detective’s skills with the power of AI.